2013
DOI: 10.2478/s13382-013-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

The level of knowledge of, attitude toward and emphasis given to HBV and HCV infections among healthcare professionals: Data from a tertiary hospital in Turkey

Abstract: Objectives:To evaluate the level of knowledge of, to investigate the attitudes toward, and to determine the emphasis given to the national prevalence of HBV/HCV infections among healthcare professionals. Materials and Methods: A total of 206 healthcare professionals (mean (SD) age: 37.0 (6.3) years; 86.9% -females) including medical laboratory technicians (N = 54) and nurses (N = 152) employed in the Antalya Training and Research Hospital, Antalya, Turkey. Laboratory (N = 53), operating room (N = 41) and in-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
2
3
0
3
Order By: Relevance
“…Among sociodemographic factors associated with increased risk of HCV infection in this study was age >37 years. These findings coincide with those of previous regional and international studies …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among sociodemographic factors associated with increased risk of HCV infection in this study was age >37 years. These findings coincide with those of previous regional and international studies …”
Section: Discussionsupporting
confidence: 93%
“…However, most studies on disease knowledge in Saudi Arabia and elsewhere have been restricted to certain population sectors, such as dental patients, medical students, healthcare providers, and rural populations . In addition, all aspects of HCV‐related knowledge were not evaluated in these surveys and the results merely demonstrated poor levels of knowledge of the epidemiology of HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely because the disease is studied as a school curriculum since healthcare workers are considered to have 2-4 fold occupational risk of hepatitis infections compared to the general population [25]. This study is similar to studies by [3] but contradict those of [26] who reported low level of knowledge among healthcare workers.…”
Section: Discussionsupporting
confidence: 80%
“…En países en los cuales se reporta una prevalencia baja (<1%) de infección por estos virus en la población general, el personal de salud desarrolla una percepción de falsa de seguridad, que contribuye a una actitud de despreocupación e incumplimiento de las medidas de seguridad y uso de implemento de protección personal (2). Otros estudios han descrito cómo la falta de conocimiento sobre la patogenicidad, el modo de transmisión y las actitudes frente al seguimiento de protocolos y normas de bioseguridad incrementan el riesgo de exposición individual que propician la presentación de accidentes laborales de riesgo biológico (5)(6)(7)(8)(9). El riesgo de infectarse con un patógeno durante la actividad laboral por lesiones percutáneas, o por el contacto con membranas mucosas o piel no intacta de sangre, tejidos u otros fluidos corporales potencialmente contaminados (5) podría ser influenciada por las actitudes y conocimiento del personal de salud frente a los riesgos que implica trabajar expuestos a diferentes categorías de patógenos (5)(6)(7)(8)(9).…”
Section: Introductionunclassified
“…Otros estudios han descrito cómo la falta de conocimiento sobre la patogenicidad, el modo de transmisión y las actitudes frente al seguimiento de protocolos y normas de bioseguridad incrementan el riesgo de exposición individual que propician la presentación de accidentes laborales de riesgo biológico (5)(6)(7)(8)(9). El riesgo de infectarse con un patógeno durante la actividad laboral por lesiones percutáneas, o por el contacto con membranas mucosas o piel no intacta de sangre, tejidos u otros fluidos corporales potencialmente contaminados (5) podría ser influenciada por las actitudes y conocimiento del personal de salud frente a los riesgos que implica trabajar expuestos a diferentes categorías de patógenos (5)(6)(7)(8)(9). En la actualidad se reportan las tasas más altas de exposición laboral por riesgo biológico en la última década debido a la exposición a la enfermedad del coronavirus 2019 (COVID-19) (10).…”
Section: Introductionunclassified